Distribution of Leguminous and Non-leguminous Nitrogen Fixing Plants in Relation to Altitudinal Variations in Eastern Part of Nepal - Singh, Himmat; , K. C.; Pokhriyal, T. C. (Indian Forester, 1998)
A chronological survey was conducted to study the identification and distribution of some nodulating and non-nodulating leguminous and actinorrhizal herb, shrub, climber and tree species in Eastern part of Nepal from Tarai (60 m) to timber-line (above 3000 m). Amongst 186 species and 79 genus explored in this study, 172 and 14 species, 70 and 9 genera were recorded in leguminous and aetinorrhizal groups. Total 144 and 7 species, 59 and 5 nodulating genera were recorded in leguminous and non-leguminous species. In the three sub-families ofLeguminoseae, Papilionoideae was recorded to offer highest number of nodulating species and Caesalpinioideae non-nodulating. However, maximum numbers of nodulating herbs, shrubs, and climbers were recorded in Papilionoideae and trees in Mimosoideae. The distribution of nodulating leguminous species were observed to be dominated in the tropical and sub-tropical areas with a sharp decline from 1800 m onwards. The maximum 92 species were observed to be occurred between 0-600 m altitudinal range, followed by 84 species between 600-1200 m, 80 species between 1200-1800 m, 48 species between 1800-2400 m, 17 species between 2400-3000 m and the minimum 5 species in and above 3000 m. These nodulating species distributed in different altitudinal ranges can be further screened for the various afforestation and soil-improvement programmes in the region.